The effect of a precoder on serially concatenated coding systems with an ISI channel. - Inkyu Lee
The performance of a serially concatenated system which includes a channel with memory preceded by a precoder as a rate-1 inner coder is presented. The effect of different precoders on the maximum-likelihood bit-error performance is analyzed. The precoder weight gain, which explains the good bit-error rate (BER) performance, is identified through a union bound analysis. Precoders are divided into two groups based on an analysis of the Euclidean distance and its multiplicity, and each precoder group shows a distinct BER curve behavior. It is shown that the BER curves for two precoder groups cross over each other. Convolutional codes are considered as outer codes in simulations on various intersymbol interference channels. Several important design considerations for the choice of precoders are derived based on the analysis and these are confirmed through simulations with an iterative decoding algorithm
Keywords: BER curves; BER performance; Euclidean distance; ISI channels; Bit-error rate; Convolutional codes; Intersymbol interference channels; Iterative decoding algorithm; Maximum-likelihood bit-error performance; Memory; Outer codes; Precoder weight gain; Random interleaver; Rate-1 inner coder; Serially concatenated coding systems; Simulations; Turbo codes; Union bound analysis